Advances in chemical engineering. - Anderson, John L. (John Leonard), 1945- (Advances in chemical engineering ;, 1996)
Volume 23 of Advances in Chemical Engineering covers the active field of process synthesis. There are currently three prevelant approaches to complex process synthesis strategies: heuristics-based selection, geometric representation, and optimization methods. This volume addresses a variety of these synthesis strategies for process subsystems, representing only a sample of the state-of-the-art of process synthesis research. The five papers in this volume address quite different process subsystems and application areas but still combine basic concepts related to a systematic approach. All five of the papers develop successful synthesis methods for their respective cutting-edge applications. As a group, the papers serve to highlight many unresolved issues in process synthesis and also provide guidelines for future research.